Evaluating the utility of socio-economic indicators to assess the resilience of smallholder agriculture to drought in Africa - Panigrahi, Niranjan; Jirasinha, Radheeka; Knox, Jerry W.; Dickens, Chris; Hess, Tim M. (IOP Publishing, 2026)
Drought is a recurrent natural hazard that significantly impacts on the livelihoods and sustainability of smallholder agriculture in Africa. A wide range of indicators have been reported in the scientific literature to support assessments of drought at multiple scales (local, regional, national) and from different perspectives, including their physical, environmental, agronomic and socio-economic (SEVI) impacts. In this study, an approach similar to a systematic review was undertaken to evaluate the range of indicators used to assess drought impacts in agriculture, with a specific focus on those that inform SEVI assessments of farmer capacities to build future resilience to drought. Based on an analysis of 355 articles from the scientific and grey literature, the majority (86%) of drought-related indicator articles were published in the last decade, with half (51%) focused on Africa and Asia. In Africa most studies were targeted at South Africa, Ethiopia and Kenya. Regarding the types of indicators used, over a quarter (27%) of studies relied on SEVI indicators with meteorological (20%), composite (19%), hydrological (12%), agricultural (8%), remote sensing (8%) and environmental (4%) indicators also being used. Most (50%) drought impact studies were conducted at the regional level, with a fifth (21%) at national and 15% at local scales, respectively. Within the literature that adopted SEVI assessments of drought, 35 different indicator types were reported. These specifically focused on vulnerability, drought resilience, coping strategies and other aspects involving indigenous knowledge, gender, risk-based and perception-based indicators, as well as various SEVI metrics. The research also identified the challenges associated with using indicators to assess drought resilience, and to support resilience frameworks, and areas for future research to inform policies to support drought risk management and sustainable agricultural development.
Keywords: climate risks; impacts; rural livelihoods; sustainability; vulnerability; 2 Zero Hunger; 37 Earth sciences; 41 Environmental sciences